Implementasi Permainan Dadu Huruf Terhadap Kemampuan Mengenal Huruf Hijaiyah pada Anak di TK Fajar Kabupaten Pangandaran - Asep Dudi Rianto; Euis Robi’ah Adawiyah (Edu Happiness : Jurnal Ilmiah Perkembangan Anak Usia Dini, 2022)
Early childhood is the age of children from 0-6 years. This period is known as the golden age, which is the golden age. The growth and development experienced by children develops rapidly in increasing their potential. At this time the child needs to be given a good stimulus, where the stimulus is given by people who are around the child, both parents, family, and an educator. Early childhood education is education given to children aged 0-6 years with efforts to guide and assist children in improving the development and growth of children, so that children have readiness to continue school in the future. In this study, there is a problem that exists in Fajar Kindergarten, Pangandaran Regency, where children do not know the hijaiyah letter, because in Fajar Kindergarten there is no learning to recognize the hijaiyah letter. Therefore, the researcher intends to implement letter dice game activities in an effort to improve children's ability to recognize Hijaiyah letters. This study uses a descriptive qualitative method with observation techniques and literature study or literature study. The results of observations made by researchers by applying the letter dice game to children in Fajar Kindergarten during (six) meetings that children can easily recognize Hijaiyah letters through letter dice games. Furthermore, the results of the literature study technique on 2 (two) journals of a researcher, that it is proven that the application of the letter dice game can affect children's recognition of the Hijaiyah letter.